Advancements in engineered exosomes for wound repair: current research and future perspectives - Ye, Hailian; Wang, Feng; Xu, Guangchao; Shu, Feihong; Fan, Kunwu; Wang, Dali (Frontiers in Bioengineering and Biotechnology, 2023)
Wound healing is a complex and prolonged process that remains a significant challenge in clinical practice. Exosomes, a type of nanoscale extracellular vesicles naturally secreted by cells, are endowed with numerous advantageous attributes, including superior biocompatibility, minimal toxicity, and non-specific immunogenicity. These properties render them an exceptionally promising candidate for bioengineering applications. Recent advances have illustrated the potential of exosome therapy in promoting tissue repair. To further augment their therapeutic efficacy, the concept of engineered exosomes has been proposed. These are designed and functionally modifiable exosomes that have been tailored on the attributes of natural exosomes. This comprehensive review delineates various strategies for exosome engineering, placing specific emphasis on studies exploring the application of engineered exosomes for precision therapy in wound healing. Furthermore, this review sheds light on strategies for integrating exosomes with biomaterials to enhance delivery effectiveness.The insights presented herein provide novel perspectives and lay a robust foundation for forthcoming research in the realm of cutaneous wound repair therapies.